Acute Acquired Methemoglobinemia Following Nitrobenzene Poisoning - Dhungel, Samriddh; Ghimire, Prabina; Shrestha, Swarup; Bhattarai, Tulsi; Pokhrel, Anil (Journal of Nepal Health Research Council, 2021)
Nitrobenzene is an aromatic compound commonly used in agricultural fertilizers. It is capable of inducing methemoglobinemia when ingested in sufficient quantities. Methemoglobinemia impairs oxygen transport by dual mechanism of impaired oxygen binding and diminished oxygen unloading. We report a case of nitrobenzene poisoning accompanied by methemoglobinemia and later complicated by unconjugated hyperbilirubinemia secondary to hemolysis. Prompt treatment with intravenous methylene blue based on a clinical diagnosis in view of dropping SpO2 unresponsive to oxygen with chocolate cyanosis and paradoxically elevated PaO2 enabled favorable patient outcome. Other recommended modalities of treatment in acquired acute methemoglobinemia include vitamin C, hyperbaric oxygen and exchange transfusions. Keywords: Methemoglobinemia; methylene blue; nitrobenzene; nitroboom